Advanced high-voltage and super-stable sodium–zinc hybrid ion batteries enabled by a hydrogel electrolyte - Debin Kong; Xinru Wei; Jinshu Yue; Changzhi Ji; Jianhang Yang; Guanzhong Ma; Xia Hu; Wenting Feng; Changming Mao; Zhongtao Li; Linjie Zhi (Energy Materials and Devices)
Aqueous secondary batteries are promising candidates for next-generation large-scale energy storage systems owing to their excellent safety and cost-effectiveness. However, their commercialization faces considerable challenges owing to a limited electrochemical stability window and lower energy density. In this study, we present a rationally designed hydrogel electrolyte, featuring a distinctive polymer network and reduced free water content, created using a UV-curing method. This innovation results in an impressive ionic conductivity of 43 mS cm−1, high mechanical strength and an enhanced electrochemical stability window of up to 2.5 V (vs. Zn/Zn2+). The hybrid electrolyte demonstrates impressive viability and versatility, enabling compatibility with various cathode materials for use in both aqueous Na–Zn hybrid batteries and Zn-ion batteries. Notably, when paired with a Prussian blue cathode, the assembled hybrid batteries show remarkable cyclability, enduring over 6000 cycles with a minimal capacity decay of only 0.0096% per cycle at a high current density of 25 C. Additionally, the Zn||Na2MnFe(CN)6 full battery using the synthesized hydrogel electrolyte achieves a high energy density of approximately 220 Wh kg−1 and outstanding rate performance reaching up to 5 C. This research provides important insights for designing aqueous hybrid electrolytes that combine both high ionic conductivity and an expansive electrochemical stability window.